Method for preparing noble metal catalyst based on precipitation reduction method
By using precipitation reduction method to immobilize precious metals on the catalytic material during the catalyst preparation process, the migration and precipitation of precious metals in high coating and high temperature environments is solved, and the anti-aging performance and preparation efficiency of the catalyst are significantly improved.
Patent Information
- Application Number
- CN202411781676.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-05
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2044-12-05
AI Technical Summary
The existing precious metal catalyst preparation methods have problems with poor noble metal migration, precipitation and anti-aging properties under high coating and high temperature environments.
The precipitation reduction method is used to precipitate precious metals on the catalytic material, and the precious metals are fixed by reducing the precious metals to avoid migration or precipitation during drying or pulping, thereby improving the anti-aging performance of the catalyst.
It effectively avoids the migration and precipitation of precious metals in high temperature environments, improves the anti-aging performance of the catalyst, simplifies the process flow, and reduces energy consumption.
Smart Images

Figure CN119425685A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of catalysts, and in particular to a method for preparing a noble metal catalyst based on a precipitation reduction method. Background Art
[0002] The existing automobile exhaust treatment technology mainly uses catalysts to remove CO, HC and NO in automobile exhaust. X These catalysts are usually made of metal oxides as carriers, on which precious metals (such as Pt, Pd, Rh, etc.) are loaded. The current industrially applicable preparation method mainly applies precious metals to metal oxide carriers by impregnation, reduction or precipitation, and then dries and calcines them at high temperature to decompose them into oxides fixed on the carrier.
[0003] On December 16, 2015, China Patent Publication No. CN105148908A disclosed an invention patent entitled "A method for preparing a supported precious metal catalyst and its application". The method uses precious metals as active components to prepare a precursor solution, and the precursor solution is mixed with the carrier evenly; a protective agent and a liquid reducing agent are added to reduce the precious metal ions adsorbed or free on the surface or in the pores of the carrier, so that the precious metal is applied to the carrier in a reduced state to obtain a mixed slurry; the mixed slurry is coated on a cordierite substrate or a metal substrate, and dried and calcined to obtain a supported precious metal catalyst. Although this method has a simple process, low energy consumption, and ensures the dispersion of precious metals, a large amount of high-polymer organic protective agents are added during the preparation process for catalysts with a high coating amount, which will rapidly decompose and release heat during calcination, causing the catalytic unit to rupture.
[0004] On July 26, 2022, China Patent Publication No. CN112691660B disclosed an invention patent entitled "A method for preparing an ammonia oxidation catalyst based on a deposition precipitation method". In this method, the precious metal oxide carrier is heat-treated in a reducing atmosphere to obtain a defective carrier and then dispersed into deionized water, ammonium carbonate solution is added for alkalization, and then the precious metal precursor solution is dripped in. After aging at room temperature, centrifugal washing and drying, the ammonia oxidation catalyst is obtained after the precious metal is calcined and solidified in a reducing atmosphere. This method requires the addition of a hydrogen reduction device and a centrifugal washing device, the process is complicated, and the precious metal solidification process also has the problem of high energy consumption of drying and calcining, and the industrial cost is relatively high. In addition, the precipitated precious metal has not yet been solidified, and the drying process will cause the migration of the precious metal, resulting in a decrease in dispersion and poor anti-aging performance.
[0005] On November 5, 2021, China Patent Publication No. CN113600188A disclosed an invention patent entitled "A Gasoline Vehicle Exhaust Purification Catalyst and Its Preparation Method". In this method, an alkaline solution is added to the Pt precursor solution until the pH value of the mixed solution is 10-12, and then applied to the carrier. After adding an acidic solution until the pH value of the mixed solution is 3-5, a mixed coating slurry is made, and the slurry is coated on a honeycomb carrier, and dried and calcined to obtain a supported precious metal catalyst. This method aims at the problem of precious metal migration in mixed slurries with multiple contents or types of precious metals, and the fact that the precious metals are not solidified during the pulping process will lead to the migration of precious metals during the drying process, resulting in a decrease in dispersion and poor anti-aging performance.
[0006] The existing preparation methods of supported catalysts all have certain limitations, so it is imperative to develop a new preparation method of supported precious metals. Summary of the invention
[0007] The purpose of the present invention is to overcome the shortcomings of the prior art and provide a method for preparing a precious metal catalyst based on a precipitation reduction method, which regulates the state of the precious metal on the catalytic material by adding a precipitant to precipitate the precious metal on the catalytic material, and then stably fixes the precious metal precipitated in situ on the catalytic material on the catalytic material by reduction, thereby avoiding the migration or precipitation of the precious metal during the drying or pulping process and the migration of the precious metal in a mixed slurry of multiple precious metals, improving the dispersion state of the active components after use in a high temperature environment, and thereby improving the anti-aging performance of the catalyst.
[0008] The purpose of the present invention is mainly achieved through the following technical solutions:
[0009] A method for preparing a noble metal catalyst based on a precipitation reduction method comprises the following steps:
[0010] Mix and disperse the catalyst material with D50 of 1-10 μm, the noble metal solution, water and the precipitant under stirring, control the pH of the mixed solution to 8-14, and stir and mature at room temperature for 1-12 hours to obtain a precipitated mixed slurry;
[0011] Dissolving a reducing agent having a molar mass of 1.1 to 5 times the amount of the precious metal in deionized water to obtain a reducing agent solution;
[0012] In a water bath at 0-90°C, add the reducing agent solution dropwise to the precipitate mixed slurry, and stir for reduction for 1-12 hours to obtain a noble metal catalyst slurry;
[0013] The noble metal catalyst slurry is mixed with a binder, an acid solution, an additive, and a thickener, and stirred for 5 to 30 minutes to obtain a coating slurry, wherein the coating slurry has a solid content of 25% to 40% and a viscosity of 1000 to 3500 mPa.s;
[0014] Sprinkling the coating slurry onto the end surface of the ceramic or metal substrate for quantitative coating;
[0015] The substrate coated with the coating slurry is dried and then calcined, and the coating slurry is solidified on the substrate to obtain a precious metal catalyst.
[0016] Furthermore, the noble metal is one or a combination of Pt, Pd, Rh, Ir, Ru, and Au, and the noble metal exists in the form of nitrate, chlorate, or organic complex salt.
[0017] Furthermore, the catalytic material is Al2O3, CeO2, ZrO2, Y2O3, La2O3, Pr6O 11 , Nd2O3, one or more mixed oxides or composite oxides, fresh specific surface area ≥ 20m 2 / g.
[0018] Furthermore, the precipitant is one or a combination of tetramethylammonium hydroxide, tetraethylammonium hydroxide, tetrapropylammonium hydroxide, tetrabutylammonium hydroxide and imine urea.
[0019] Furthermore, the reducing agent is one or a combination of ascorbic acid, glucose, fructose, maltose, formaldehyde, formic acid, ethylene glycol, and glycerol.
[0020] Furthermore, the acid solution is one or more of glacial acetic acid, dilute nitric acid, and oxalic acid.
[0021] Furthermore, the binder is one of aluminum sol and zirconium sol or a mixture of the two, the binder mass fraction is 20%-25%, D50 is 2-20nm, and pH is 2-5.
[0022] Furthermore, the auxiliary agent is one of barium salt and strontium salt or a mixture of the two.
[0023] Furthermore, the thickener is one or a mixture of more than one of methyl cellulose, carboxymethyl cellulose, hydroxyethyl cellulose and hydroxypropyl methyl cellulose.
[0024] Furthermore, the coating slurry is a mixed slurry of one or more noble metal catalyst slurries, and the coating dry basis coating amount is 10-350 g / L.
[0025] In summary, the present invention has the following beneficial effects compared with the prior art:
[0026] 1. Compared with the existing process, the catalyst prepared by the present invention can fix the precious metal in situ at the pre-precipitated position, avoiding the migration or precipitation of the precious metal during the drying or pulping process and the migration of the precious metal in the mixed slurry of multiple precious metals, and can improve the dispersion state of the active components after use in a high temperature environment, thereby improving the anti-aging performance of the catalyst.
[0027] 2. In the method of the present invention, no high-polymer organic matter is added during the catalyst preparation process, thereby avoiding the cracking of the carrier during the calcination process of the catalyst unit.
[0028] 3. The present invention adopts a one-step slurrying process, which reduces the drying, calcining and fixing process after the precious metal loading. The operation process is simple, the energy consumption is low, and it is easy to realize industrial-scale production. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] The drawings described herein are used to provide a further understanding of the embodiments of the present invention, constitute a part of this application, and do not constitute a limitation of the embodiments of the present invention. In the drawings:
[0030] Figure 1 Schematic diagram of the change in the conversion rate of CO to fresh catalyst of Example 1 and Comparative Example 1 in the embodiments of the present invention as a function of temperature;
[0031] Figure 2 Schematic diagram of the change in NO conversion rate of fresh catalysts of Example 1 and Comparative Example 1 in the embodiments of the present invention with temperature;
[0032] Figure 3 Schematic diagram of the change in conversion rate of THC by fresh catalyst of Example 1 and Comparative Example 1 in the embodiments of the present invention with temperature;
[0033] Figure 4 Schematic diagram of the change in CO conversion rate of the aged catalysts of Example 1 and Comparative Example 1 in the embodiments of the present invention as a function of temperature;
[0034] Figure 5 Schematic diagram of the change in NO conversion rate of the aged catalysts of Example 1 and Comparative Example 1 in the embodiments of the present invention with temperature;
[0035] Figure 6 Schematic diagram of the change in conversion rate of THC by the aged catalyst of Example 1 and Comparative Example 1 in the embodiments of the present invention as a function of temperature;
[0036] Figure 7 It is a process flow chart of the present invention. DETAILED DESCRIPTION
[0037] In order to make the objectives, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with embodiments and drawings. The exemplary implementation modes of the present invention and their description are only used to explain the present invention and are not intended to limit the present invention.
[0038] like Figure 7 As shown, a method for preparing a precious metal catalyst based on a precipitation reduction method comprises the following steps: mixing and dispersing a catalytic material with a D50 of 1-10 μm, a precious metal solution, water and a precipitant under stirring, controlling the pH of the mixed solution to be 8-14, and stirring and aging at room temperature for 1-12 hours to obtain a precipitated mixed slurry; dissolving a reducing agent with a molar mass of 1.1-5 times the amount of the precious metal in deionized water to obtain a reducing agent solution; and adding the reducing agent solution dropwise to the precipitated mixed slurry in a water bath at 0-90°C. The method comprises the steps of: stirring and reducing for 1-12 hours to obtain a noble metal catalyst slurry; mixing the noble metal catalyst slurry with a binder, an acid solution, an additive, and a thickener, and stirring for 5-30 minutes to obtain a coating slurry, wherein the coating slurry has a solid content of 25% to 40% and a viscosity of 1000 to 3500 mPa.s; pouring the coating slurry on the end face of a ceramic or metal substrate for quantitative coating; drying the substrate coated with the coating slurry and then calcining it, and then solidifying the coating slurry on the substrate to obtain a noble metal catalyst.
[0039] Furthermore, the noble metal is one or a combination of Pt, Pd, Rh, Ir, Ru, and Au, and the noble metal exists in the form of nitrate, chlorate, or organic complex salt.
[0040] Furthermore, the catalytic material is Al2O3, CeO2, ZrO2, Y2O3, La2O3, Pr6O 11 , Nd2O3, one or more mixed oxides or composite oxides, fresh specific surface area ≥ 20m 2 / g.
[0041] Furthermore, the precipitant is one or a combination of tetramethylammonium hydroxide, tetraethylammonium hydroxide, tetrapropylammonium hydroxide, tetrabutylammonium hydroxide and imine urea.
[0042] Furthermore, the reducing agent is one or a combination of ascorbic acid, glucose, fructose, maltose, formaldehyde, formic acid, ethylene glycol, and glycerol.
[0043] Furthermore, the acid solution is one or more of glacial acetic acid, dilute nitric acid, and oxalic acid.
[0044] Furthermore, the binder is one of aluminum sol and zirconium sol or a mixture of the two, the binder mass fraction is 20%-25%, D50 is 2-20nm, and pH is 2-5.
[0045] Furthermore, the auxiliary agent is one of barium salt and strontium salt or a mixture of the two.
[0046] Furthermore, the thickener is one or a mixture of more than one of methyl cellulose, carboxymethyl cellulose, hydroxyethyl cellulose and hydroxypropyl methyl cellulose.
[0047] Furthermore, the coating slurry is a mixed slurry of one or more noble metal catalyst slurries, and the coating dry basis coating amount is 10-350 g / L. It should be noted that the coating dry basis coating amount is the coating amount of the substrate after calcination.
[0048] To further illustrate the present application, the present application is described below through more specific embodiments and comparative examples.
[0049] Embodiment 1:
[0050] In the stirring state, the fresh specific surface area is 80m 2 / g, 99gCe-Zr material with a D50 of 6μm is dispersed in deionized water; palladium nitrate solution (1g in terms of palladium oxide) is dissolved in deionized water, and the treated palladium nitrate solution and tetramethylammonium hydroxide are added to the mixed slurry through a peristaltic pump to adjust the pH value of the mixed solution to 11, and stirred and aged at room temperature for 3h to obtain a precipitated mixed slurry, and a formic acid solution (the stoichiometric ratio with the precious metal is 2:1) is diluted with deionized water to obtain a reducing agent solution; the reducing agent solution is added to the above-mentioned precipitated mixed slurry through a peristaltic pump, The catalyst was reduced by stirring at room temperature for 2 hours to obtain a noble metal catalyst slurry; 6.25g of dilute nitric acid, 24.3g of barium acetate, 0.5g of carboxymethyl cellulose and 25g of aluminum sol with a mass fraction of 25%, D50 of 10nm and pH of 3 were added to the noble metal catalyst slurry and stirred for 20 minutes, and water was added to adjust the solid content to obtain a coating slurry with a solid content of 35% and a viscosity of 2690mPa.s; the coating slurry was applied to a cordierite substrate, dried at 150°C for 2 hours, and calcined at 550°C for 2 hours to obtain catalyst 1. The remaining coating slurry was divided into two groups, one group was filtered, washed, dried at 150°C for 2 hours, calcined at 550°C for 2 hours, and then sampled to test the content of noble metal palladium, which was recorded as A, and the other group was sampled to test the dispersion of noble metal palladium, which was recorded as B.
[0051] Embodiment 2:
[0052] In the stirring state, the fresh specific surface area is 80m 2 / g, 49.5gCe-Zr material with a D50 of 6μm and a fresh specific surface area of 140m 2 / g, 49.5gLa-Al material with a D50 of 6μm was dispersed in deionized water; palladium nitrate solution (1g in terms of palladium oxide) was dissolved in deionized water and divided into two parts, and the treated palladium nitrate solution and tetramethylammonium hydroxide were added to the Ce-Zr material slurry and La-Al material slurry through peristaltic pumps to adjust the pH to 11, and stirred and aged at room temperature for 3h, and then formic acid (the stoichiometric ratio with the precious metal was 2:1) solution was diluted with deionized water and divided into two parts, and the Ce-Zr material slurry and La-Al material slurry were added through peristaltic pumps. La-Al material slurry, and stirred and reduced at room temperature for 2h, respectively obtaining mixed slurries E and F; slurry E and slurry F were mixed, 6.25g of dilute nitric acid, 24.3g of barium acetate, 0.5g of carboxymethyl cellulose and 25g of aluminum sol with a mass fraction of 25%, D50 of 10nm, and pH of 3 were added and stirred for 20min, and water was added to adjust the solid content to obtain a coating slurry with a solid content of 35% and a viscosity of 3150mPa.s; the coating slurry was applied to a cordierite substrate, dried at 150°C for 2h, and calcined at 550°C for 2h to obtain catalyst 2. The remaining coating slurry was divided into two groups, one group was filtered, washed, dried at 150°C for 2h, calcined at 550°C for 2h, and then sampled to test the content of precious metal palladium, recorded as A, and the other group was sampled to test the dispersion of precious metal palladium, recorded as B.
[0053] Comparative Example 1:
[0054] Tetramethylammonium hydroxide was added to adjust the pH of the palladium nitrate solution (1 g of palladium oxide) to 11.0, and the treated palladium nitrate precursor solution was loaded onto a fresh surface area of 80 m 2 / g of 99gCe-Zr material, dried at 120℃ for 2h, and calcined at 550℃ for 2h. The calcined catalyst was stirred for 20min with 200g water, 6.25g dilute nitric acid, 24.3g barium acetate, 0.5g carboxymethyl cellulose and 25g aluminum sol with a mass fraction of 25%, D50 of 10nm, and pH of 3 to obtain a coating slurry with a solid content of 35% and a viscosity of 1860mPa.s; the coating slurry was applied to a cordierite substrate, dried at 150℃ for 2h, and calcined at 550℃ for 2h to obtain catalyst R1. The remaining coating slurry was divided into two groups, one group was filtered, washed, dried at 150℃ for 2h, calcined at 550℃ for 2h, and then sampled to test the content of precious metal palladium, recorded as A, and the other group was sampled to test the dispersion of precious metal palladium, recorded as B.
[0055] Comparative Example 2:
[0056] In the stirring state, the fresh specific surface area is 80m 299g Ce-Zr material with a mass fraction of 25%, a D50 of 10nm and a pH of 3 was dispersed in deionized water, tetramethylammonium hydroxide was added through a peristaltic pump to adjust the pH to 11, palladium nitrate solution (1g in terms of palladium oxide) was dissolved in deionized water, the treated palladium nitrate solution was added to the mixed slurry through a peristaltic pump, and the pH was fine-tuned to 11 with a tetramethylammonium hydroxide solution with a concentration of 0.1mol / L, and stirred at room temperature for 5h, and then 6.25g dilute nitric acid, 24.3g barium acetate, 0.5g carboxymethyl cellulose and 25g aluminum sol with a mass fraction of 25%, a D50 of 10nm and a pH of 3 were added and stirred for 20min, and water was added to adjust the solid content to obtain a coating slurry with a solid content of 35% and a viscosity of 2730Pa.s. The coating slurry was applied to a cordierite substrate, dried at 150°C for 2h, and calcined at 550°C for 2h to obtain catalyst R2. The remaining coating slurry was divided into two groups. One group was filtered, washed, dried at 150°C for 2 hours, calcined at 550°C for 2 hours, and then sampled to test the content of precious metal palladium, recorded as A; the other group was sampled to test the dispersion of precious metal palladium, recorded as B.
[0057] Comparative Example 3:
[0058] In the stirring state, the fresh specific surface area is 80m 2 99g of Ce-Zr material with a mass fraction of 0.1mol / L and a D50 of 6μm was dispersed in deionized water, and tetramethylammonium hydroxide was added through a peristaltic pump to adjust the pH to 11. A palladium nitrate solution (1g in terms of palladium oxide) was dissolved in deionized water, and the treated palladium nitrate solution was added to the mixed slurry through a peristaltic pump, and the pH was finely adjusted to 11 with a tetramethylammonium hydroxide solution with a concentration of 0.1mol / L, and stirred at room temperature for 5h, filtered, washed, dried at 150℃ for 2h, and calcined at 550℃ for 2h. The calcined catalyst was stirred with 200g of water, 6.25g of dilute nitric acid, 24.3g of barium acetate, 0.5g of carboxymethyl cellulose and 25g of aluminum sol with a mass fraction of 25%, a D50 of 10nm, and a pH of 3 for 20min to obtain a coating slurry with a solid content of 35% and a viscosity of 2050mPa.s. The coating slurry was coated on a cordierite substrate, dried at 150°C for 2h, and calcined at 550°C for 2h to obtain catalyst R3. The remaining coating slurry was divided into two groups, one of which was filtered, washed, dried at 150°C for 2h, calcined at 550°C for 2h, and then sampled to test the content of precious metal palladium, recorded as A, and the other group was sampled to test the dispersion of precious metal palladium, recorded as B.
[0059] Comparative Example 4:
[0060] In the stirring state, the fresh specific surface area is 80m 2 / g, 99gCe-Zr material with D50 of 6μm is dispersed in deionized water, and then palladium nitrate solution (calculated as 1g of palladium oxide) is dissolved in deionized water, and the treated palladium nitrate solution is added to the above Ce-Zr material slurry by a peristaltic pump, and stirred for 3h, and PVP (the stoichiometric ratio with the precious metal is 3:1) protective agent and formic acid (the stoichiometric ratio with the precious metal is 2:1) reducing agent are gradually added by a peristaltic pump, and stirred for reduction at room temperature for 2h, 6.25g of dilute nitric acid, 24.3g of barium acetate, 0.5g of carboxymethyl cellulose and 25g of aluminum sol with a mass fraction of 25%, D50 of 10nm, and pH of 3 are added and stirred for 20min, and water is added to adjust the solid content to obtain a coating slurry with a solid content of 35% and a viscosity of 2250mPa.s. The coating slurry is applied to a cordierite substrate, dried at 150°C for 2h, and calcined at 550°C for 2h to obtain catalyst R4. The remaining coating slurry was divided into two groups. One group was filtered, washed, dried at 150°C for 2 hours, calcined at 550°C for 2 hours, and then sampled to test the content of precious metal palladium, recorded as A; the other group was sampled to test the dispersion of precious metal palladium, recorded as B.
[0061] Comparative Example 5:
[0062] In the stirring state, the fresh specific surface area is 80m 2 / g, 49.5gCe-Zr material slurry with a D50 of 6μm and a fresh specific surface area of 140m 2 / g, 49.5g La-Al material slurry with D50 of 6μm was dispersed in deionized water respectively; palladium nitrate solution (calculated as palladium oxide, 1g) was dissolved in deionized water and divided into two parts, and the treated palladium nitrate solution and tetramethylammonium hydroxide were added to the Ce-Zr material slurry and La-Al material slurry through peristaltic pumps to make the pH to 11, and stirred and matured at room temperature for 5h to obtain slurries C and D; slurry C and slurry D were mixed, and 6.25g dilute nitric acid, 24.3g barium acetate, 0.5g carboxymethyl cellulose and 25g aluminum sol with a mass fraction of 25%, D50 of 10nm and pH of 3 were added and stirred for 20min, and water was added to adjust the solid content to obtain a coating slurry with a solid content of 35% and a viscosity of 3100mPa.s. The coating slurry was coated on a cordierite substrate, dried at 150°C for 2h, and calcined at 550°C for 2h to obtain catalyst R5. The remaining coating slurry was divided into two groups. One group was filtered, washed, dried at 150°C for 2 hours, calcined at 550°C for 2 hours, and then sampled to test the content of precious metal palladium, recorded as A; the other group was sampled to test the dispersion of precious metal palladium, recorded as B.
[0063] It should be noted that in the examples and comparative examples of the present application, the substrates for catalyst coating are 118.41*80 / 400cpsi cordierite, volume 0.8805L, coating dry basis coating amount 88.3g / L, precious metal loading 0.706g / L; The content of precious metals is determined by ICP to determine the concentration of precious metals in the coating slurry, and the precious metal loading rate G is calculated to obtain a comparison table of the content of precious metals in the slurry coating of the embodiment and the comparative example, as shown in Table 2. Precious metal loading rate (G) = Precious metal concentration in the coating after washing, drying and calcining of the slurry coating (A) / theoretical precious metal concentration in the coating (H).
[0064] Table 1 Comparison of catalyst preparation processes of Examples and Comparative Examples
[0065]
[0066] Table 2 Comparison of precious metal content in coatings of examples and comparative examples
[0067]
[0068]
[0069] As can be seen from Table 1 and Table 2, compared with Example 1, Example 1 adopts a one-step pulping process, which reduces the drying and calcining process of the precious metal fixing process, and greatly reduces energy consumption. Compared with Example 2, Example 1 further fixes the precious metal on the catalytic material by reduction on the basis of precipitation, solves the problem of precious metal precipitation in the pulping process, and significantly improves the precious metal loading rate in the coating. Compared with Example 3, Example 1 further fixes the precious metal on the catalytic material by reduction on the basis of precipitation, which solves the problem of high energy consumption in the precious metal solidification process. Compared with Example 4, Example 1 fixes the precious metal on the catalytic material by first precipitation and then reduction, avoids the use of high-polymer organic protective agents, and solves the risk of unit rupture during the calcination process of the catalytic unit. Compared with Example 5, Example 2 fixes the precious metals on the corresponding catalytic materials by first precipitation and then reduction, avoids the problem of precious metal precipitation and migration in the slurry mixing process, improves the precious metal loading rate, and enables the catalytic material and the corresponding precious metal to achieve better matching.
[0070] In the examples and comparative examples of the present application, two 1in*1in cylinders were taken from each substrate for activity testing, wherein the aged samples were obtained by aging at 950°C in an air atmosphere for 10 hours.
[0071] Dispersion test conditions:
[0072] Referring to the method of eliminating CeO2 in Shen M's literature, CO2 was used to remove the interference of Ce on precious metals and then CO-Pulse was used to test the dispersion of precious metals.
[0073] Literature: Shen M, Wei G, Yang H, et al. Different selections of active sites for CO, C3H6, and C10H22 oxidation on Pd / CeO2 catalysts[J]. Fuel, 2013, 103: 869-875.
[0074] Activity test conditions:
[0075] Atmosphere: CO4500ppm, NO1250ppm, CO211.0%, H2O10.0%, O23800ppm, C3H6220ppm, C3H8110ppm, H21500ppm, N2 as balance gas, λ=1, space velocity 40000h -1 After activating at 600℃ for 2h, the temperature was lowered to below 150℃ for transient temperature test, with a heating rate of 5℃ / min. In the following table, T50 is the temperature corresponding to 50% conversion rate, also known as the ignition temperature, and T90 is the temperature corresponding to 90% conversion rate, also known as the complete conversion temperature. The reaction formula of each component is as follows:
[0076] CO+O2—CO2; HC+O2—H2O+CO2; NO+CO+HC—N2+CO2+H2O
[0077] Table 3 Comparison of precious metal dispersion between the examples and the comparative examples
[0078]
[0079] Table 4 Comparison of catalyst activities of various embodiments and comparative examples
[0080]
[0081] As can be seen from the data in Table 3, there is little difference in the fresh dispersion of the precious metals in the prepared slurry coatings compared with Comparative Examples 1-4 and Comparative Example 2 and Comparative Example 5, but after the state of the precious metals on the catalytic material is effectively regulated and solidified by the precipitation reduction method, the aged dispersion of the precious metals in the prepared slurry coatings is improved to a certain extent. It can be further seen from the performance data in Table 4 that the fresh and aged ignition temperatures and complete conversion temperatures of CO / THC / NO in the examples are reduced, that is, the catalytic conversion efficiency is improved. In Comparative Example 1, since the size of the precious metal is not regulated during the loading process, the precious metal is embedded after high-temperature aging and the anti-aging performance is poor. In Comparative Examples 2 and 5, the precious metal is not effectively fixed, resulting in the agglomeration of the precious metal particles after high-temperature aging and poor anti-aging performance. In Comparative Example 3, the precious metal is fixed on the catalytic material by drying and calcining, but the drying process will cause the migration of the precious metal, so the anti-aging performance is poor. In Comparative Example 4, the size of the precious metal is regulated by reduction and fixed on the catalytic material, and the anti-aging performance is better, but more organic matter needs to be added during the process. In the embodiments, the size of the precious metal is first regulated by pre-precipitation to make it precipitate on the catalytic material, and then the precious metal is fixed by in-situ reduction. The whole process effectively regulates the precious metal and improves the aging dispersion of the precious metal, thereby further improving the anti-aging performance of the catalyst.
[0082] like Figures 1 to 3 As shown, the conversion rate of fresh catalysts of Example 1 and Comparative Example 1 to CO, NO, and THC changes with temperature; wherein the ordinate represents the conversion rate, in %, and the abscissa represents the temperature, in ℃; Curve A and Curve B are the changes of fresh samples of Example 1 and Comparative Example 1, respectively. Figures 4 to 6 , are the changes in the conversion rates of CO, NO and THC of the aged catalysts of Example 1 and Comparative Example 1 with temperature; wherein the ordinate represents the conversion rate, in %, and the abscissa represents the temperature, in ℃; curves Aa and Ba are the changes in the aged samples of Example 1 and Comparative Example 1, respectively.
[0083] from Figure 1 to Figure 6 It can be clearly seen that compared with Comparative Example 1, the fresh and aged catalysts of Example 1 have better ignition performance and high-temperature conversion rate of CO, NO, and THC than those of Comparative Example 1. This indicates that the catalyst of the present invention has excellent ignition performance and anti-aging performance.
[0084] The specific implementation methods described above further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific implementation method of the present invention and is not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.
Claims
1. A method for preparing a noble metal catalyst based on a precipitation reduction method, characterized in that: The following steps are involved: Mix and disperse the catalyst material with D50 of 1-10 μm, the noble metal solution, water and the precipitant under stirring, control the pH of the mixed solution to 8-14, and stir and mature at room temperature for 1-12 hours to obtain a precipitated mixed slurry; Dissolving a reducing agent having a molar mass of 1.1 to 5 times the amount of the precious metal in deionized water to obtain a reducing agent solution; In a water bath at 0-90°C, add the reducing agent solution dropwise to the precipitate mixed slurry, and stir for reduction for 1-12 hours to obtain a noble metal catalyst slurry; The noble metal catalyst slurry is mixed with a binder, an acid solution, an additive, and a thickener, and stirred for 5 to 30 minutes to obtain a coating slurry, wherein the coating slurry has a solid content of 25% to 40% and a viscosity of 1000 to 3500 mPa.s; Sprinkling the coating slurry onto the end surface of the ceramic or metal substrate for quantitative coating; The substrate coated with the coating slurry is dried and then calcined, and the coating slurry is solidified on the substrate to obtain a precious metal catalyst.
2. The method for preparing a noble metal catalyst based on a precipitation reduction method according to claim 1, characterized in that: The noble metal is one or a combination of Pt, Pd, Rh, Ir, Ru, and Au, and the noble metal exists in the form of nitrate, chlorate, or organic complex salt.
3. The method for preparing a noble metal catalyst based on a precipitation reduction method according to claim 1, characterized in that: The catalytic material is Al2O3, CeO2, ZrO2, Y2O3, La2O3, Pr6O 11 , Nd2O3, one or more mixed oxides or composite oxides, fresh specific surface area ≥ 20m 2 / g.
4. The method for preparing a noble metal catalyst based on a precipitation reduction method according to claim 1, characterized in that: The precipitant is one of tetramethylammonium hydroxide, tetraethylammonium hydroxide, tetrapropylammonium hydroxide, tetrabutylammonium hydroxide and imine urea, or a combination of several of them.
5. The method for preparing a noble metal catalyst based on a precipitation reduction method according to claim 1, characterized in that: The reducing agent is one or a combination of ascorbic acid, glucose, fructose, maltose, formaldehyde, formic acid, ethylene glycol, and glycerol.
6. The method for preparing a tail gas treatment catalyst according to claim 1, characterized in that: The acid solution is one or more of glacial acetic acid, dilute nitric acid, and oxalic acid.
7. The method for preparing a tail gas treatment catalyst according to claim 1, characterized in that: The binder is one of aluminum sol and zirconium sol or a mixture of the two, the mass fraction of the binder is 20%-25%, the D50 is 2-20nm, and the pH is 2-5.
8. The method for preparing a tail gas treatment catalyst according to claim 1, characterized in that: The auxiliary agent is one of barium salt and strontium salt or a mixture of the two.
9. The method for preparing a tail gas treatment catalyst according to claim 1, characterized in that: The thickener is one or a mixture of methyl cellulose, carboxymethyl cellulose, hydroxyethyl cellulose and hydroxypropyl methyl cellulose.
10. The method for preparing a tail gas treatment catalyst according to claim 1, characterized in that: The coating slurry is a mixed slurry of one or more noble metal catalyst slurries, and the coating dry basis coating amount is 10-350g / L.
Citation Information
Patent Citations
Preparation method and application of supported noble metal catalyst
CN105148908A
A method for preparing ammonia oxidation catalyst based on deposition precipitation method
CN112691660B
Purification catalyst for tail gas from gasoline car and preparation method of purification catalyst
CN113600188A
Active component morphology controllable loaded noble metal catalyst and preparation method thereof
CN102553581A
DOC catalytic coating with high fuel oil ignition performance and preparation method thereof
CN111617773A